Migratory Movements of Homo Faber: Mapping Fab Labs in Latin America - Sperling, David M. (2015)
Conference: 16th International Conference, CAAD Futures 2015 - "The next city". São Paulo, Brazil, July 8-10, 2015, At São Paulo, Brazil., Volume: Computer-Aided Architectural Design Futures. The Next City - New Technologies and the Future of the Built Environment ( Communications in Computer and Information Science, Volume 527 - 2015)